Chillers: The Haunting of Nadia - Jarman, Julia (Penguin Group, 1998)
Nadia looked out into the wet November afternoon.She didn't want to go past the pond in the dark. In fact,she didn't want to go past the pond at all.
Keywords: Horror & Ghost Stories; Juvenile Fiction